Survival and prognostic differences between appendiceal NETs and goblet cell adenocarcinomas - Dijke, Kim; van den Berg, José; Kuhlmann, Koert F D; Levy, Sonja; Valk, Gerlof D; Tesselaar, Margot E T (BioScientifica Ltd., 2025)
Objective: Patients with appendiceal neuroendocrine tumours (aNETs) have an excellent prognosis. Appendiceal goblet cell adenocarcinomas (aGCAs), formerly called goblet carcinoid, show overlapping features with aNETs. Many discrepancies exist between studies regarding prognostication of patients with aNETs. In this study, we aim to identify differences in disease course between aNETs and aGCAs to explain inconsistencies in the literature and identify variables influencing recurrence and survival. Methods: Patients with aNET or aGCA diagnosed between 2000 and 2019 were included. Kaplan–Meier curves were performed in patients with aNET and aGCA independently and in a combined group covering both aNETs and aGCAs to assess progression-free survival (PFS) and disease-specific survival (DSS). Cox regression was used to identify variables influencing PFS and DSS. Results: In total, 122 patients were included: 92 with aNET and 30 with aGCA. Five-and 10-year PFS rates in patients with aNET were both 98%, whereas in patients with aGCA, this was 57% and 30%, respectively. The 5-and 10-year DSS rates for aNETs were 100 and 96%, and for aGCAs, this was 77 and 58%. In the combined group, 5-and 10-year DSS were 92 and 84%, and the presence of peritoneal metastases showed worse DSS (P < 0.001). WHO grade 3 was associated with poorer PFS (HR 18.68, 95% CI (2.24–155.59), P = 0.007) and DSS (HR = 10.21, 95% CI (1.23–85.08), P = 0.032) in aGCAs. Conclusion: aNETs and aGCAs are different entities with a distinct prognosis. Differences in DSS between aNETs and aGCAs indicate previous studies misclassified aggressive tumours as aNETs, which addresses the importance of accurate tumour registration and reckoning with changes in nomenclature.
Keywords: Journal Article